Competencias disciplinares, didácticas e investigativas: un estudio del docente ecuatoriano de Química - Quevedo Reyes, Liz Karol (2024)
The principal objective of this research is to evaluate the competencies of chemistry teachers in Ecuador. The disciplinary, didactic and research competencies acquired by teachers in this subject are analyzed and examined. The methodological process used was fieldwork, whose technique was a Likert-type survey that evaluated these three specific competencies. It was emailed to approximately 150 teachers in the area of natural sciences in the subject of chemistry, but only answered thirty. The results reveal that, about disciplinary competencies, 80% of respondents say they totally agree and according with the development of these skills. In terms of teaching skills, 92% agree and strongly agree that the application of various methodological strategies contributes to improving the educational environment. With regard to research competencies, 75% of teachers state that they agree or strongly agree. 15% remain in a neutral position and 5% disagree with competencies, which proposes the need, in the future, to dialog and reflect on the reasons for the relative importance of building these aspects in the educational process. It means that for teachers research is still not the priority, but didactics is, even above disciplinary knowledge, that is, chemical knowledge. Keywords: competencies; Didactic; Disciplinary; Research.